Pola Komunikasi Pengasuh dalam Menegakkan Kedisiplinan Santri Pondok Pesantren Modern Daar Al-Uluum Kisaran - Nabhan, Alfitri Adeny; Zainun, Zainun; Efendi, Erwan (ANWARUL, 2024)
The aim of this research is to determine the communication patterns of the mujahideen assembly in broadcasting Islamic law in the city of Medan and to determine the obstacles and supporting factors for the mujahideen assembly in broadcasting Islamic law in the city of Medan. The method in this research is to use a qualitative method where the researcher goes directly to the field and interviews the sources or informants of this research face to face. The results of this research are the communication patterns used by supervisors in enforcing student discipline at the Daar Al-Uluum Kisaran Modern Islamic Boarding School, Kisaran, Asahan Regency, namely Interpersonal Communication Patterns and Group Communication Patterns. The factor that is an obstacle to carrying out the dhuha prayer discipline is the lack of self-confidence of the students towards their caregivers at the Daar Al-Uluum Modern Islamic Boarding School which results in the caregivers/guides not knowing the problems experienced by the students. The closed nature of a santri makes it difficult for caregivers/coaches to know what problems the santri are experiencing. There is still a lack of creating a harmonious relationship between all elements of caregivers at the Daar Al-Modern Islamic Boarding School and the Santri. This less than harmonious relationship occurs because the students who have just entered still don't know the students and their caregivers/guides as a whole and there is still a sense of embarrassment (awkwardness) among the students, especially the students who have just entered, when dealing directly with the caregivers/guides at the Daar Al Modern Islamic Boarding School. -Uluum Kisaran, Asahan Regency.